#### Answer

(a) 3
(b) 3

#### Work Step by Step

We are given: $f(x)=3x-2$, $x=2,x=3$
(a) We calculate the net change:
$f(3)-f(2)=[3*3-2]-[3*2-2]=7-4=3$
(b) We calculate the average rate of change:
$\displaystyle \frac{f(3)-f(2)}{3-2}=\frac{3}{1}=3$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

(a) 3
(b) 3

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.